Birmanie (Myanmar) 2010-2017 : un pays en transition ? - Candier, Aurore (AsieS, 2020)
After several decades under military dictatorship, Burma (Myanmar) entered a period of political transition in 2010. Following a new constitution in 2008, the military regime held elections and handed power over to a "semi-civilian" government. Former general Thein Sein was elected president in 2011 and implemented major democratic reforms. The elections of 2015 continued to confirm the political changes when the charismatic opposition leader Aung San Suu Kyi came to power. What is the actual nature of these seemingly dramatic changes, and what are their limits? This collection of essays brings unique perspectives to the change Burmese society underwent from 2010-2017, rather than focusing solely on the "democratization," given so much attention in previous English-language scholarship on the political transition in Burma. Here French scholars of Burma bring their in-country experience as anthropologists, geographers and historians to reflect on the transition, offering interpretations of the continuities and discontinuities with the past, while providing new readings of the present. The essays cover the influence of local forces against external factors in bringing about change and reforms; transformations in land governance; the continuing need to include ethnic minorities in education reform; and the deep connections between Buddhist nationalism, communal violence, and the Rohingya crisis.